Optimasi Waktu Dan Massa Ca(OH)2 Pada Proses Recovery NaOH Dari Na2CO3 Produk Samping Produksi Silika Dari Fly Ash Sawit (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Sodium hydroxide is one of the basic chemicals that has an important role in the production process such as silica. NaOH is used as a solvent to dissolve the silica present in the palm fly ash. NaOH recovery is an alternative to reduce production costs. This study aims to determine the NaOH recovery process in the manufacture of silica from palm fly ash. NaOH is recoveredusing the caustification method by reacting the by-product Na2CO3 with Ca(OH)2. The variables studied were 40 minutes (lowest) and 100 minutes (highest); and the mass of Ca(OH)2 is 30 gr (lowest) and 50 gr (highest). The fixed variables used were Na2CO3 0.5 L; stirring speed of 500rpm and temperature of 85oC. The caustic solution was analyzed by titration to determine % NaOH and % Na2CO3. RSM-CCD was used to determine the optimum conditions for the NaOH recovery process. The results showed that the optimum operating conditions were 90.2 minute and the mass of Ca(OH)2 was 54.14 gr.Keywords :NaOH, optimization, palm fly ash, RSM, caustification.